S-nitroso-N-acetylcysteine attenuates liver fibrosis in experimental nonalcoholic steatohepatitis [Corrigendum] - Mazo DF; de Oliveira MG; Pereira IV; Cogliati B; Stefano JT; de Souza GF; Rabelo F; Lima FR; Ferreira Alves VA; Carrilho FJ; de Oliveira CP (Dove Medical Press, 2013)
Mazo DF, de Oliveira MG, Pereira IV, Cogliati B, Stefano JT, de Souza GF, Rabelo F, Lima FR, Ferreira Alves VA, Carrilho FJ, de Oliveira CP. Drug Des Devel Ther. 2013:7:553–563. On page 554, the sentence "Therefore, we chose SNAC as a potential antifibrinogenic NO donor drug for treating fibrosis..." contains an error. The term "antifibrinogenic" should be replaced by "antifibrogenic". On page 558, Figure 3 (D), the intermediate block corresponding to SNAC is missing. View original paper by Mazo et al